SEMINAR ETIKA BERINTERNET DI SMA MUHAMMADIYAH KOTA BOGOR - Chairiansyah, Syafril (PT Triputra Sejahtera Prima, 2025)
The Community Service (PKM) activity for the even semester of the 2024-2025 academic year was proposed by our group, lecturers from the Informatics Engineering Department of Pamulang University (UNPAM). This activity will be held at SMA Muhammadiyah Kota Bogor. Community Service is part of the Tri Dharma of Higher Education and is mandatory every semester. The theme of this PKM activity is the Internet Ethics Seminar at SMA Muhammadiyah Kota Bogor. This seminar introduces internet ethics so students can understand ethical online interactions and their implications for everyday life. In addition, students are introduced to cybercrime so they understand these crimes and how to avoid them. The target output of the community service program implemented at SMA Muhammadiyah Kota Bogor is to increase students' understanding of internet ethics and its dangers. Photos of the activity, articles in print or online media, and journal articles are available.